Dynamic Extracellular Imaging of Biochemical Cell Activity Using InGaN/GaN Nanowire Arrays as Nanophotonic Probes. (1st August 2018) - Hölzel, Sara; Zyuzin, Mikhail V.; Wallys, Jens; Pouokam, Ervice; Müßener, Jan; Hille, Pascal; Diener, Martin; Parak, Wolfgang J.; Eickhoff, Martin
Abstract: The application of InGaN/GaN nanowire heterostructure arrays as photonic probes for dynamic imaging of biochemical and cellular processes in an incident light fluorescence microscope is demonstrated. The photoluminescence intensity of InGaN/GaN nanowires sensitively depends on the pH value of the surrounding solution, making them suitable probes for the optical detection of biochemical processes accompanied by local pH variations. Grown on a conductive substrate, the nanowire arrays can be operated in a well‐defined electrochemical working point with high sensitivity and stability. The achievable pH and bias resolution as well as signal‐to‐noise ratio are assessed as a function of the working point and for different integration times. A bias resolution of 1 mV and a pH resolution of 0.03 are achieved at a time resolution below 25 ms. The application for dynamic imaging of the activity of isolated intestinal crypts from Wistar rats is demonstrated. Here, the pH change in the vicinity of the crypt is quantified and attributed to the activity of the sodium‐proton exchanger (NHE). Imaging of the effect of amiloride and NH4 Cl on its activity is demonstrated with a spatial resolution of <0.63 µm and reveals that NH4 Cl‐induced NHE activation preferentially occurs in the upper part of the crypt. Abstract : This research reports the dynamic imaging of biochemical and cellular processes using InGaN/GaN nanowire heterostructures as nanophotonic probes. The unique combination of chemical surface properties and efficient photoluminescence makes biased InGaN/GaN nanowire electrodes an excellent tool for imaging local pH changes due to biochemical reactions in a standard fluorescence microscope.